EFFECT OF CHROMIUM CONTENT ON MECHANICAL PROPERTIES OF NICKEL-FREE AUSTENITIC STAINLESS STEELS - Jasmin Halilović; Edis Nasić; Derviš Mujagić (Journal of Sustainable Technologies and Materials)
This study investigated the mechanical properties of a series of Fe-Cr-Mn (Mo)-N alloys. The chromium content ranged from 16 to 18 mass %. The test alloys were produced by adding nitrided ferroalloys during melting in an induction furnace. Test specimens of each alloy were prepared for mechanical testing and microstructural observation. Tensile strength (TS) and elongation (EL) were determined. By increasing or decreasing the content of the chromium, it can directly affected on the values of the mechanical properties and the final microstructure. A series of experiments showed that increasing the chromium content by 1.46 mass% in the Fe-16Cr-8Mn (Mo)-N alloy led to a decrease in the TS value by 12% and in the EL value by 16.1%, while increasing the chromium content by 0.72 mass% in the Fe-16Cr-11Mn (Mo)-N alloy caused a decrease in the TS value by 6.1% and in the EL value by 16%. The chromium content of 16 mass % in the studied alloys was found to provide sufficient strength and a relatively high elongation value. The alloys can also contain a higher mass fraction of chromium, but to obtain a complete austenitic structure it is necessary to increase the content of manganese and nitrogen.